Antioxidants and antiaging properties of methanol and aqueous extracts of Bougainvillea glabra leaves / Aina Nadhira Aziz - Aziz, Aina Nadhira (2023)
Skin aging caused by photoaging, is a serious skin-health concern including in Malaysia as this affects individual of all ages due to the continuous exposure to high UV radiation annually. Currently, there are a wide range of cosmetic products available. However, since most of these are available over the counter, the efficacy of these products is unclear as these products are less regulated. In addition, some of these products contain toxic ingredients such as mercury, hydroquinone, tretinoin, and azelaic acid that may exacerbate the skin condition. Therefore, recent studies revealed that most consumers prefer natural-based products. The main purpose of this study is to assess the antioxidant and antiaging activities of Bougainvillea glabra. The samples were extracted using two different solvents, namely absolute methanol and aqueous using maceration method. Antioxidant activity was assessed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging assay, resulting in an average of 76.403 ± 10.158% for methanolic extracted while aqueous extract of B. glabra showed an average of 50.912± 12.194%. The antiaging activities were assessed using tyrosinase assays following with an average of 32.032 ± 5.699% for methanolic extract and aqueous extract with average of 27.35 ± 3. 938%. The antiaging activities correlated with the level of anti-tyrosinase activities. Overall, the study shows that methanol and aqueous extracts of B. glabra leaves exhibited potent antioxidant property and moderate level of anti-tyrosinase activity. Successful completion of this study may result in a novel skincare formulation using B. glabra leaf extract which can be beneficial to those with chronic skin problems. This study also adds new knowledge on the medicinal property of B. glabra.